1986
DOI: 10.1159/000183849
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the Renal Involvement in Mixed Cryoglobulinemia with Prolonged Plasma Exchange

Abstract: Nine patients with mixed cryoglobulinemia and severe membranoproliferative glomerulonephritis were treated with plasma exchange alone or in combination with medium to low amounts of corticosteroids, but never with cytotoxic drugs. In 5 patients renal function and/or proteinuria improved after plasma exchange, and no clinical relapse usually occurred when the procedures were reduced or discontinued. These procedures seemed of particular effect in the presence of histologically active and not irreversible lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 12 publications
(20 reference statements)
0
41
0
3
Order By: Relevance
“…Moreover, the presence of ge nomic sequences, indicating the ongoing HCV multiplication, was found in all sub jects investigated by PCR. Light microscopy, showing hypercellular lobulated glomeruli, thickened capillary walls and frequent 'dou ble contours', intraluminal thrombi and/or pseudothrombi, confirmed that renal in volvement of MC is invariably characterized by a type 1 MPGN [14], This is an immune complex glomerulonephritis that may in volve either classical or alternate pathways of complement activation. This is proved by the identification of complement compo nents (C3, C4, C lq) and immunoglobulins in glomerular basement membranes using the immunofluorescence technique and of electron-dense deposits in the subendothelial side, corresponding to immune complex deposition in the capillary walls, by electron microscopy [15].…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, the presence of ge nomic sequences, indicating the ongoing HCV multiplication, was found in all sub jects investigated by PCR. Light microscopy, showing hypercellular lobulated glomeruli, thickened capillary walls and frequent 'dou ble contours', intraluminal thrombi and/or pseudothrombi, confirmed that renal in volvement of MC is invariably characterized by a type 1 MPGN [14], This is an immune complex glomerulonephritis that may in volve either classical or alternate pathways of complement activation. This is proved by the identification of complement compo nents (C3, C4, C lq) and immunoglobulins in glomerular basement membranes using the immunofluorescence technique and of electron-dense deposits in the subendothelial side, corresponding to immune complex deposition in the capillary walls, by electron microscopy [15].…”
Section: Discussionmentioning
confidence: 70%
“…Затем на протяжении не-скольких десятилетий с этой целью назначались НПВП и глюко-кортикостероиды (ГКС) в низких дозах, а при тяжелом течении (гломерулонефрит, невропатия, системный васкулит) проводи-лась монотерапия в более высоких дозах или в комбинации с ци-тостатиками и/или экстракорпоральными методами (ПА, криоа-ферез), что остается стандартом лечения до последнего времени [23,24].…”
Section: терапевтический архив 6 2015unclassified
“…Thus some patients are left with plasmapheresis as the only available therapeutic option or others may need plasmapheresis until these other therapies take hold. Ferri et al [30] showed that some patients with cryoglobulinemia may respond to plasmapheresis alone (Table III).…”
Section: Cryoglobulinemiamentioning
confidence: 99%